Stress Medication with 2D Game and Al-Quran Reading: Mobile application for relieve the stress - Rosali, Ainur Faten Syamimi; Wan Ismail, Wan Shazlina (Journal of Computing Technologies and Creative Content, 2021)
This research was carried out to resolve the need for a Final Year Project at UNIKL MIIT before the academic year ends inJanuary 2021. The Bachelor of Interactive Multimedia Design (BIMD) programme allowed students to create a professional application. "Mobile Application: Stress Medication with 2D Game and Al Quran Reading," the researcher decides to develop a mobile app. The aim of this app is to make the user feel less stressed." This app has a "3 in 1" design, which means it will include stress content, a 2D game, and Al-Quran recitation. Since most mobile apps don't know how to deal with stress and don't combine stress management, Al-Quran recitation, and game play into one app, this app was made. As a result, the aim of this project is to look at existing stress-relieving apps and develop an interactive app with a 2D game and Quran recitation to help people relax. The ADDIE Model was used to create the methodology for this app. The application's efficacy will be evaluated using a questionnaire and a scaling method. Additionally, Unity programming is used in this app. The app is easy to use and has a smart capture feature. Audible musicals have been included to add to the charm of this mobile application. This is an effort to motivate students and employees to play 2D games and recite the Quran to forget about their worries while having endless fun.